Bioinspired Construction of Ruthenium-decorated Nitrogen-doped Graphene Aerogel as an Efficient Electrocatalyst for Hydrogen Evolution Reaction - Shi Y. (Springer Berlin Heidelberg, 2020)
10.1007/s40242-020-0167-2